Jaws. 3 [videorecording (Blu-Ray)] - Quaid, Dennis; Armstrong, Bess; MacCorkindale, Simon, 1952-2010; Gossett, Louis, Jr., 1936- (Universal Pictures Home Entertainment, 2016)
Everyone at Florida's Sea World is thrilled with the new "Undersea Kingdom", a maze of underwater plexiglass tunnels that permits visitors to get closer to marine life than ever before. The opening ceremonies include many important guests, and one uninvited baby shark that accidentally enters the park's lagoon through a faulty sea gate and subsequently dies. The young shark's 35-foot mother soon follows her offspring, creating the most horrifying tale of terror ever filmed in the water.